3y-6x=-33

Simple and best practice solution for 3y-6x=-33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y-6x=-33 equation:


Simplifying
3y + -6x = -33

Reorder the terms:
-6x + 3y = -33

Solving
-6x + 3y = -33

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3y' to each side of the equation.
-6x + 3y + -3y = -33 + -3y

Combine like terms: 3y + -3y = 0
-6x + 0 = -33 + -3y
-6x = -33 + -3y

Divide each side by '-6'.
x = 5.5 + 0.5y

Simplifying
x = 5.5 + 0.5y

See similar equations:

| F[x]=2x+12 | | -10w=15 | | x(x+4)=6(2) | | 9=v+6-2 | | (5x)=-18 | | (2x+20)=(3x-10) | | 3(2x+1)-5x=2(x+1)-3 | | (2x-20)=(3x-10) | | 15=12x^2+24x | | 4d+8-2d=6d-10 | | -12x+2y=x+2 | | 7xy-4xy+2xy+6xy+3xy-7xy= | | 14x-(3x-7)=40 | | f(n)=2*f(n-1) | | 3(3z+1)-8=40 | | -1440=-15(-15x-29) | | 8u-1=8 | | (6+k)+12=23 | | 3(2x-7)-4(x-1)= | | 2h+10=66 | | 2h+10=66 | | y-8+124=180 | | -41=5x+9 | | -1440=-15(-15x-21) | | 1.4a+10=17 | | 6x+13=5x | | n+36=5m | | (X-3)(x+4)=x^2-5x+20 | | 9+2z-8=7z+7-4z | | a(-12)=b | | 0.6x-0.33=1 | | 4000=5.5x-460.5 |

Equations solver categories